Approximation approach to multiple singularities of flow through a porous pipe with decelerating wall - Rouf, RA; Alam, MS; Khan, MAH (Journal of Naval Architecture and Marine Engineering, 2012)
The multiple singularity behaviour of flow through a porous pipe with decelerating wall is numerically studied in the present paper. The behaviour of the Riccati equation is introduced as a model problem. Then the steady axisymmetric flow of a viscous incompressible fluid driven along a pipe by the combined effect of the wall deceleration and suction is investigated. Our approach uses the power series in order to observe the instability of the problems. The series is then summed by using various generalizations of the Pade´-Hermite approximants. Analysis based on approximate method suggests that the convergence of the series of stream-function, skin friction and centerline axial velocity in powers of Reynolds number is limited by a number of singularities. The location and nature of the singularities in the real plane are presented. The bifurcations of skin friction and centerline axial velocity are also depicted graphically. DOI: http://dx.doi.org/10.3329/jname.v9i1.9283 Journal of Naval Architecture and Marine Engineering 9(2012) 35-42